2016
DOI: 10.1002/lno.10395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metatranscriptomics reveals decline of a neustonic planktonic population

Abstract: The neuston layer in tropical seas provides a good model to study the effects of increased levels of different stressors (e.g., temperature, ultraviolet radiation and Trichodesmium blooms). Here, we use a comparative in situ metatranscriptomics approach to reveal the functional genomic composition of metabolically active neustonic mesozooplankton community in response to the summer conditions in the Red Sea. The neustonic population exhibited changes in composition and abundance with a significant decline in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…S6 ) and no enhanced mortality, i.e. increased numbers of carcasses could be observed in our samples being in contrast to other recent findings 30 . Apart from surface avoidance behavior, a typical response of copepods to UV stress 31 , and possessing sun screening carotenoids such as astaxanthin, emerging work has shown that UV-protective mycosporine-like amino acids (MAA) have an important role in UV protection of near-surface (top 50 cm) zooplankton communities 32 .…”
Section: Resultscontrasting
confidence: 95%
“…S6 ) and no enhanced mortality, i.e. increased numbers of carcasses could be observed in our samples being in contrast to other recent findings 30 . Apart from surface avoidance behavior, a typical response of copepods to UV stress 31 , and possessing sun screening carotenoids such as astaxanthin, emerging work has shown that UV-protective mycosporine-like amino acids (MAA) have an important role in UV protection of near-surface (top 50 cm) zooplankton communities 32 .…”
Section: Resultscontrasting
confidence: 95%
“…Environmental transcriptomics of planktonic organisms has contributed new insights into niche separation and led to new hypotheses to explain rapid changes in abundances (Alexander et al, 2015; Mojib et al, 2017). Neocalanus flemingeri is well suited for environmental transcriptomics: it has a single generation per year with an annual phenology that is predictable and synchronized with the annual spring phytoplankton bloom (Cooney, 1986; Cooney et al, 2001; Coyle et al, 2019; Coyle & Pinchuk, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, viruses were found attached to mesozooplankton, e.g., collected from the neuston of the Red Sea using a Manta neuston net that sampled the top 1 m of the water column [ 92 ]. Due to observed high mortality of copepods (phylum Arthropoda) in their samples, the authors were looking for VLPs on Acartia fossae, a blue-pigmented surface-dwelling copepod, and its prey, Trichodesmium cells.…”
Section: Viral Dispersal In and Out Of The Smlmentioning
confidence: 99%